The Portuguese Validation of the Basic Psychological Need Satisfaction and Frustration Scale: Concurrent and Longitudinal Relations to Well-being and Ill-being. Issue 3 (13th July 2016) - Cordeiro, Pedro; Paixão, Paula; Lens, Willy; Lacante, Marlies; Luyckx, Koen
This research comprises two studies based on Self Determination Theory. In Study 1, we translate and examine the factor structure of the Basic Psychological Needs Satisfaction and Frustration Scale (BPNSFS;Chen, Vansteenkiste et al., 2015 ) in a sample of Portuguese undergraduate students. Further, in Study 2 we used an independent longitudinal sample of 12 th grade students to inspect whether the six subscales differently predict adjustment over time. Confirmatory factor analysis showed that a six-factor solution best fitted the BPNSFS data. Subsequent structural equation modelling indicated that the dimensions of need satisfaction and need frustration predicted unique variance in participants' well-being and ill-being over time, even after controlling for reciprocal and baseline effects. Taken together the findings support the 6-factor multidimensional structure of the BPNSFS and provide extensive support for the distinction between the satisfaction and frustration dimensions of needs, suggesting that they should be measured and interpreted as relatively distinct motivational constructs.